ANALISIS KEPUASAN KERJA KARYAWAN PADA PT. CITRA KARYA INTI SENTOSA I JAMBI - Misna Misna (Jurnal Dinamika Manajemen, 2015)
This study aims to get an overview of employee job satisfaction at PT.Citra Karya Inti Sentosa 1 Jambi and to analyze the factors of job satisfaction at PT.Citra Karya Inti Sentosa 1 Jambi. This study took a sample of 23 employees of PT Citra Karya Inti Sentosa 1 Jambi using the survey method. The method used to analyze the data generated from this research is descriptive qualitative analysis. The results of this study show an overview of employee job satisfaction at PT. Citra Karya Inti Sentosa 1 Jambi, based on the results of the survey and analysis carried out it can be concluded that the average proportion of the factors that influence job satisfaction at PT. Citra Karya Inti Sentosa 1 Jambi is based on calculations Data processing starts from the work factor itself which has an unsatisfied rating scale, and on the personality suitability factor which has a dissatisfied rating scale. Overall, employee job satisfaction is not good. It can be seen that job satisfaction factors such as the work itself, salary, working conditions, co-workers, and personality satisfaction have not been met properly. For the progress and sustainability of PT. Citra Karya Inti Sentosa 1 Jambi, the author will later suggest that the factors of job satisfaction can be cultivated even better.